Immunohistochemical study of placental lactogen in the trophoblast in immaturity of the chorionic tree of the placenta on the background of iron deficiency anemia in pregnant women - Olena Tiulienieva; Igor Davydenko; Viallanta Tiulienieva; Olena Marchuk; Tetiana Shelest; Oleksandr Volkov (Kazimierz Wielki University, 2021)
The study of placental lactogen by immunohistochemistry in histological sections of the placenta during physiological pregnancy and on the background of iron deficiency anemia in the aspect of chronic placental insufficiency. It is established that during gestation against the background of iron deficiency anemia decreases the production of placental lactogen by syncytiotrophoblast of the chorionic villi and correlates with the state of the blood of the pregnant woman. The optical density of immunohistochemical staining for placental lactogen of the free trophoblast reflects the degree of maturation of the chorionic tree of the placenta in iron deficiency anemia in pregnant women. Chronic placental insufficiency caused by immaturity of the chorionic villi can be compensated at the level of metabolism.